Formation of Recreational Areas in the Natural Landscape Areas of Uzbekistan (In the Example of the Fergana Region) (Journal of Architectural Design, 2022)
Uzbekistan attracts foreign tourists with its unique and beautiful nature and ancient and rich cultural heritage. This provides an opportunity for further development of ecotourism in our country. In the Fergana region, large-scale work is being done on the development of ecotourism. Favourable conditions have been created for tourists to have fun in the heart of nature, enjoy the beauty, and get acquainted with rare examples of flora and fauna. Especially in the Fergana region.